Akad Pembiayaan Ijarah Muntahiya bit-Tamlik (Leasing) di BMT Sidogiri Cabang Situbondo: Perspektif Maqashid Syari’ah - Umi Khoiriyah; Khairul Umam Al-Basit (Program Pascasarjana Universitas Ibrahimy, 2017)
This research is under several reasons: First, the contradiction between as-sunnah and IMBT implementation cause differences opinion among of ulama. Second, the recommendation from the director of BMT to resolve this problem and how IMBT can interested more customers the next time. The focus of this research is: 1). How is the implementation of leasing in Sidogiri BMT?, 2). How is the implementation of leasing in Sidogiri BMT according on Maqashid Mu’amalah perspective? The theory of maqashid in this research is belongs to “Maqashid Mu’amalah wa Marashidul Waqi’at” by Abdullah Ibn Bayyah. The reason this theory is more relevant to the content and data of this research. The conclusion is In leasing procedural, BMT supply a thing, that thing is rent to the members, BMT promise that it will sell that thing in the last time of rental tempo. The Tamlik transaction is implemented in the last tempo of rental tempo.